Addressing fears of children with Williams syndrome: therapist and child behavior in the context of a novel play-and humor-infused exposure therapy approach - Young, Brianna N.; Mohanty, Ellora; Levine, Karen; Klein-Tasman, Bonita P. (Frontiers in Psychology, 2023)
Many children with Williams syndrome struggle with fears and phobias that significantly impact their daily lives. Yet, there is sparse literature about the impact of behavioral interventions to treat anxiety and phobias among children with Williams syndrome. Using observational coding of intervention videos, the current study examines patterns of the therapist's use of play and humor and relations to child behavioral responses for 4 children with Williams syndrome who were identified as treatment responders to humor and play-infused exposure therapy for fears and anxieties. Sessions were coded for therapist behaviors (exposure with or without play/humor, stimulus type used during exposure, passive or invited attention to feared stimulus, and spontaneous parent participation in exposure) as well as positive, negative, and neutral child behaviors (verbalizations, behaviors). Temporal patterns between therapist and child behaviors were analyzed using lag sequential analyses. Results showed that tolerance of feared stimuli improved for 2 of the 4 children following this playand humor-infused exposure therapy approach, and the remaining 2 participants demonstrated progress beyond tolerating the feared stimulus and showed increased positive behaviors with the feared stimulus across sessions. Findings also showed patterns of therapist attunement to the child's anxiety level demonstrated through efforts to flexibly adjust the degrees of exposure. Therapistinitiated invited attention behaviors, indicative of the therapist's use of narration and priming, were associated with child tolerance and positive behaviors during exposure to the feared stimulus. Limitations of this study include a very small sample size, short duration of intervention, and a single-subject research design, which limit the generalizability of findings. Implications and future directions of this research are discussed.